Pregnancy complicated with adrenal adenoma causing ACTH-independent Cushing’s syndrome, accompanied by obstetric antiphospholipid syndrome and severe pre-eclampsia: case report and literature review - Xu, Shenghan; Liu, Miao; Xu, Jiamu; Che, Bangwei; Zhang, Wenjun; Li, Wei; Huang, Tao; Yu, Ying; Zha, Cheng; Peng, Zheng; Huang, Kunyuan; Tang, Kaifa (Frontiers in Endocrinology, 2023)
This case report shares the management experience of a patient with pregnancy combined with adrenal adenoma causing ACTH-independent Cushing’s syndrome (CS), accompanied by obstetric antiphospholipid syndrome (OAPS) and severe pre-eclampsia. The case was a 26-year-old that presented with typical clinical symptoms and signs of CS. The patient had a history of 4 spontaneous abortions in the last 4 years. The 24-hour urinary free cortisol was significantly increased, an abnormal cortisol circadian rhythm was demonstrated by a high late-night salivary cortisol, blood ACTH was suppressed (< 1ng/dL), anticardiolipin antibody was positive, and imaging examination showed an adrenal tumor. The patient underwent laparoscopic adrenal tumor resection under general anesthesia at 23 weeks of gestation. The tumor was pathologically confirmed to be an adrenocortical adenoma. The patient underwent a cesarean section at 39 weeks of gestation to give birth to a healthy baby girl with an Apgar score of 10. Pregnancy complicated by CS is clinically rare, easily masked by normal physiological changes of pregnancy, and is difficult to diagnose. The determination of 24-hour urinary free cortisol, the circadian rhythm of serum cortisol, ultrasound, and MRI can be helpful in the diagnosis of CS during pregnancy. Surgery is the first choice for the treatment of CS during pregnancy. As a subtype of antiphospholipid syndrome, patients with OAPS are prone to thrombotic events and recurrent miscarriages if not treated accordingly. To our knowledge no cases of CS with OAPS and severe pre-eclampsia have been reported. We summarize the experience of the treatment of this patient and review the literature to improve clinicians’ awareness of this disease.